2022
DOI: 10.12775/qs.2022.08.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Perceived Usefulness and Fitness Wearable Technology User Adoption Mediated by Culture, Gender, and COVID-19: A Meta-Analysis

Abstract: With COVID-19 raging and individuals exercising at home, the adoption of fitness wearable technology (FWT) that help people monitor their physical state has become a pressing matter. Here, we try to bridge the gap that no researcher has examined the link between perceived usefulness (PU) and FWT adoption by using meta-analysis to comprehend the detailed numerical values and moderating factors affecting the relationship. A total of 24 articles with 7180 re-pendants were investigated from January 1, 2015 to Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The Technology Acceptance Model (TAM) applied in previous studies highlights the importance of perceived ease of use in determining the actual system use and, by extension, the perceived value of the technology. For instance, a study found that perceived ease of use positively correlates with the accessibility scale of Gratifications of Wearables Technology, indicating that easier-to-use wearable technologies are more likely to be adopted and valued by users [ 54 ]. This is further supported by findings that simple operation and appearance design significantly impact the perceived ease of use of sports wearable devices, which in turn affects users' attitudes and behaviors towards these devices [ 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The Technology Acceptance Model (TAM) applied in previous studies highlights the importance of perceived ease of use in determining the actual system use and, by extension, the perceived value of the technology. For instance, a study found that perceived ease of use positively correlates with the accessibility scale of Gratifications of Wearables Technology, indicating that easier-to-use wearable technologies are more likely to be adopted and valued by users [ 54 ]. This is further supported by findings that simple operation and appearance design significantly impact the perceived ease of use of sports wearable devices, which in turn affects users' attitudes and behaviors towards these devices [ 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, a study found that perceived ease of use positively correlates with the accessibility scale of Gratifications of Wearables Technology, indicating that easier-to-use wearable technologies are more likely to be adopted and valued by users [ 54 ]. This is further supported by findings that simple operation and appearance design significantly impact the perceived ease of use of sports wearable devices, which in turn affects users' attitudes and behaviors towards these devices [ 54 ]. Moreover, the perceived ease of use has been identified as a critical factor in users' acceptance of the multidimensional health and fitness features of wrist-worn wearable devices (WWDs), suggesting that when users find fitness functions easy to use without causing any difficulty, they tend to use those functions more [ 55 ].…”
Section: Literature Reviewmentioning
confidence: 99%